Sifat dan Karakteristik Hukum Islam - Nur Sa’adah Harahap; Uswatun Hasanah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This research explains what is included in the nature and character of Islamic law. The research method used in this research is a literature study, namely the data used in this research comes from books and journals that discuss the philosophy of Islamic law. The nature and characteristics of Islamic law include perfect (Takamul), elastic, universal, dynamic and systematic. Although Islam has clear and firm laws, but by knowing some of the properties and characteristics of Islamic law, the rules of Islamic law itself are not rigid. Islamic law can very easily adjust to the conditions of the times and places.